On the road: Communicating traffic. (March 2019) - De Stefani, Elwys; Broth, Mathias; Deppermann, Arnulf
Abstract: How do people communicate in mobile settings of interaction? How does mobility affect the way we speak? How does mobility exert influence on the manner in which talk itself is consequential for how we move in space? Recently, questions of this sort have attracted increasing attention in the human and social sciences. This Special Issue contributes to the emerging body of studies on mobility and talk by inspecting an ordinary and ubiquitous phenomenon in which communication among mobile participants is paramount: participation in traffic. This editorial presents previous work on mobility in natural settings, as carried out by interactionally oriented researchers. It also shows how the investigation into traffic participation adds new perspectives to research on language and communication.